PERANCANGAN DAN PEMBUATAN SEPEDA LISTRIK PENGISIAN DAYA OTOMATIS DENGAN MENGGUNAKAN MOTOR DC SEBAGAI SUMBER ENERGI ALTERNATOR - ismail, Normansyah (entries, 2024)
With the development of technology in two-wheeled motorized vehicles, especially in the drive or transmission system, which is currently dominated by automatic transmissions (Automatic Transmission), slowly, began to replace manual transmissions (Manual Transmission). In terms of motor driving, innovation in the use of alternative energy continues to develop, where the use of an internal combustion engine (BBM) will gradually be replaced by an electric motor as the main driver by utilizing a source of electrical energy stored in the battery. Moving on from the above thought, the author tries to apply the workings of